Intimidade no relacionamento terapeuta-cliente: alcances e limites - Coppede, Angélica Silva Marden (2007)
In the present research, we verified how eight behavior therapists with differing age, experience and from different geographical regions deal with closeness and intrusiveness by the client in their personal life. The occurrence of questions or comments by the clients that make the therapist talk about particularities of his or her life: The effects these have on the therapist and the therapist-client relationship, what variables control the therapist s behavior of responding to these questions, or, summing up: possibilities for coping and clinical intervention. The study uses a qualitative, explanatory approach, using semi-structured interviews for data-collection. The interviews were transcribed for analysis according to the Grounded Theory model, an inductive strategy that consists in organizing, categorizing and interpreting data that lead to the construction of a theory that explains the studied phenomenon. The results indicate that therapists make intentional use of emerging clinical situations, like questions by the therapist about his or her private life. The reaction of the therapist to questions about his or her private life can, depending on the therapist, be converted in interventions and make the relationship more intimate; and this may be directly linked to the professional repertoire the therapist has in coherence with what is proposed by treatment models like Functional Analytical Psychotherapy (FAP) and Therapy through the Contingencies of Reinforcement (TCR). FAP facilitates the comprehension and classifications of behaviors emitted by the client as clinically relevant behaviors and promotes the acceptance by the therapist of the byproducts of the interaction, not evaluating them as negative, but as opportunities in the session for the development of the relationship. TCR prioritizes the consciousness both therapist and client have, concerning the contingencies that are operating in the different contexts of the client s life, and emphasizes the importance of the therapist to be able to describe the adopted strategies.